QSAR Modeling of Acute Neurotoxicity of Some Organic Solvents with Respect to Rodents - Grigorev, V.Yu.; Raevskaya, O.E.; Yarkov, A.V.; Raevsky, O.A. (Biomedical Chemistry: Research and Methods, 2018)
Using literature data analysis, the regression models of acute sublethal neurotoxicity of 47 organic solvents with respect to rats and mice have been developed. To construct the models, we used linear regression, random forest and support vector machines approaches. The linear regression equations were selected as the best models. They are designed on the basis of four molecular descriptors: polarizability, sum of positive atom charges, sum of proton acceptor descriptors and dipole moment. The developed models have good descriptive and predictive ability and clear physicochemical interpretation.